Association of hepatocellular carcinoma with thiazolidinediones use: A population-based case-control study. Issue 17 (April 2020) - Lai, Shih-Wei; Lin, Cheng-Li; Liao, Kuan-Fu
Abstract : Abstract: The study aimed to investigate the association between the risk of hepatocellular carcinoma and thiazolidinediones use among type 2 diabetic patients who had risk factors for hepatocellular carcinoma. A population-based case-control study was performed using the database of the Taiwan National Health Insurance Program. The cases consisted of 23580 type 2 diabetic subjects aged 20 to 84 years with newly diagnosed hepatocellular carcinoma between 2000 and 2011. The sex- and age-matched controls consisted of 23580 randomly selected type 2 diabetic subjects without hepatocellular carcinoma between 2000 and 2011. Ever use of thiazolidinediones was defined as subjects who had at least 1 prescription of thiazolidinediones before the index date. Never use of thiazolidinediones was defined as subjects who did not have a prescription of thiazolidinediones before the index date. The odds ratio and 95% confidence interval for the association between hepatocellular carcinoma and cumulative duration of thiazolidinediones use was measured by a multivariable logistic regression model. Among subjects with any 1 of the comorbidities including alcohol-related disease, cirrhosis, hepatitis B infection, hepatitis C infection, and other chronic hepatitis, a multivariable logistic regression model demonstrated that there was a negative association between hepatocellular carcinoma and every 1-year increase of cumulative duration of thiazolidinediones use (adjusted odds ratio 0.94, 95% confidence interval 0.92–0.97). There was a negative association in a duration-dependent manner between the risk of hepatocellular carcinoma and thiazolidinediones use among type 2 diabetic patients who had risk factors for hepatocellular carcinoma.